2019
DOI: 10.2169/internalmedicine.1697-18
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic and Hormonal Effects of Tolvaptan for Heart Failure

Abstract: Tolvaptan (TLV) is a diuretic agent administrated for heart failure (HF) only in Japan. Many clinical findings have been obtained from the accumulation of clinical experience, and the administration of TLV reportedly avoids causing a reduction in the renal function. In addition, TLV has been reported to exert effects other than diuresis. The early start of TLV after hospitalization shortens the length of the hospital stay, and continuous TLV after discharge extends the period until re-hospitalization of HF pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 50 publications
0
0
0
Order By: Relevance
“…Clinical practices have shown that tolvaptan can effectively improve the symptoms of HF patients compared with traditional loop diuretic therapy. [14][15][16] In addition to improving cardiac performance, tolvaptan was thought to enhance renal function by encouraging water excretion with electrolyte-free. 17) In- travascular volume depends on serum osmotic pressure and colloid osmotic pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical practices have shown that tolvaptan can effectively improve the symptoms of HF patients compared with traditional loop diuretic therapy. [14][15][16] In addition to improving cardiac performance, tolvaptan was thought to enhance renal function by encouraging water excretion with electrolyte-free. 17) In- travascular volume depends on serum osmotic pressure and colloid osmotic pressure.…”
Section: Discussionmentioning
confidence: 99%